2010
DOI: 10.1353/eca.2010.0015
|View full text |Cite
|
Sign up to set email alerts
|

How Useful Are Estimated DSGE Model Forecasts for Central Bankers?

Abstract: Dynamic stochastic general equilibrium (DSGE) models are a prominent tool for forecasting at central banks, and the competitive forecasting performance of these models relative to alternatives, including official forecasts, has been documented. When evaluating DSGE models on an absolute basis, however, we find that the benchmark estimated mediumscale DSGE model forecasts inflation and GDP growth very poorly, although statistical and judgmental forecasts do equally poorly. Our finding is the DSGE model analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 36 publications
5
120
0
Order By: Relevance
“…This is because the inflation process has become markedly less persistent than before, and is now dominated by short-run fluctuations. The findings in Edge and Gürkaynak (2010) are in line with this, since they find that their DSGE model is very poor at forecasting US inflation, but so are all the other approaches that they use (uni-and multivariate time series models).…”
Section: Conclusion and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This is because the inflation process has become markedly less persistent than before, and is now dominated by short-run fluctuations. The findings in Edge and Gürkaynak (2010) are in line with this, since they find that their DSGE model is very poor at forecasting US inflation, but so are all the other approaches that they use (uni-and multivariate time series models).…”
Section: Conclusion and Discussionsupporting
confidence: 72%
“…They also provide the standard baseline in the assesment of the forecasts from DSGE models, see e.g. Edge and Gürkaynak (2010). The results of the comparison are presented in Section 6.3, while Section 7 contains our conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…If the model predicts that policymaker actions are useless, it is no surprise that policymakers were not exactly clamouring to take them on board. A second major reason for the delayed uptake by central banks was that the forecasting record for these models was poor and policymakers preferred models that tracked the data more reliably, even if at the cost of theoretical consistency (Edge and Gürkaynak 2010;Gürkaynak et al 2013). As highly abstract and highly theoretical tools, these models did not offer much help in the crucial task of forecasting.…”
Section: A History Of Macroeconomic Modelling In Central Banksmentioning
confidence: 99%
“…Basco, D'Amato, and Garegnani (2009) analyze money with price relationship for Argentia and found that money and price relationship holds during high inflationary period. (EDGE & GÜRKAYNAK, 2010), forecast the monetary policy mechanism for Turkey and explain that, inflation deviation are unpredictable for Turkey. Moreover, (DSGE) and Bayesian VAR model proves poor forecasting for the Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, it is not a least demanding task to measure inflation volatility in order to craft systematic behaviour for different market players. Although different studies have been done so for to measure the inflation volatility such as ((EDGE & GÜRKAYNAK, 2010 ;Berument & Sahin, 2010;Berganza & Broto, 2012;Castillo, 2014;Singor, Grzelak, van Bragt, & Oosterlee, 2013;Ginindza & Maasoumi, 2013;Clark & Davig, 2011;Kim, 2004;Castelnuovo, 2010)) that provide an overview and postulate that under unsystematic monetary policy inflation deviation is unpredictable, while for systematic monetary policy, it is desirable to assume that government does not intervene in the monetary policy. In this paper, we choose a mathematical technique to measure inflation volatility and inflation prediction for Turkey.…”
mentioning
confidence: 99%